2009
DOI: 10.1103/physrevb.80.195311
|View full text |Cite
|
Sign up to set email alerts
|

Electronic reconstruction at a buried ionic-covalent interface driven by surface reactions

Abstract: Lattice-matched ionic NaCl films were grown layer by layer on covalent Ge͑100͒ using cycles of two half reactions ͑HRs͒ that involved the alternative adsorption of Cl and Na. The Ge 3d photoemission spectra obtained after full cycles of growth resembled that of clean Ge͑100͒, but came to resemble that of the polar Cl-terminated surface after the subsequent half reaction of Cl adsorption. Concurrently, the Na and Cl core levels of the nanofilms shifted by ϳ1.7 eV between these two interface configurations. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 24 publications
(22 reference statements)
1
10
1
Order By: Relevance
“…5, we see that W 3 appears to saturate to a scale-independent constant at large L as the transition is approached from the Néel phase, before growing with size as one moves into a columnar VBS state. This near-marginal behaviour of the anisotropy in P (E Ψ ) at the largest scales accessible to our simulations is very different from the U (1) symmetric probability distribution of E Ψ seen near the square lattice critical point [18,19]. A more refined scaling analysis [41] yields the same result, leading us to our earlier suggestion that three-fold monopole insertions are (very close to) marginal at the NCCP 1 critical point-this is consistent with recent parallel work that discusses relevance of q-fold monopoles in SU(N ) spin models [44,45].…”
Section: Pacs Numberscontrasting
confidence: 79%
See 1 more Smart Citation
“…5, we see that W 3 appears to saturate to a scale-independent constant at large L as the transition is approached from the Néel phase, before growing with size as one moves into a columnar VBS state. This near-marginal behaviour of the anisotropy in P (E Ψ ) at the largest scales accessible to our simulations is very different from the U (1) symmetric probability distribution of E Ψ seen near the square lattice critical point [18,19]. A more refined scaling analysis [41] yields the same result, leading us to our earlier suggestion that three-fold monopole insertions are (very close to) marginal at the NCCP 1 critical point-this is consistent with recent parallel work that discusses relevance of q-fold monopoles in SU(N ) spin models [44,45].…”
Section: Pacs Numberscontrasting
confidence: 79%
“…In addition, we find evidence for apparently logarithmic violations of finite-temperature scaling of the uniform spin susceptibility χ u and stiffness ρ s , analogous to the square-lattice case [17]. However, in sharp contrast to the square-lattice transition at which the four-fold anisotropy vanishes for large systems [18][19][20], a careful study of the three-fold anisotropy in the phase of Ψ reveals surprising nearmarginal behaviour on the honeycomb lattice. The honeycomb lattice has a two-site basis (labeled A and B) and elementary Bravais lattice trans-lationsê1 andê2, with distances from origin specified in units ofê1 andê2.…”
Section: Pacs Numbersmentioning
confidence: 62%
“…[4][5][6][7] A scanning tunneling microscopy (STM) measurement suggests that the growth of NaCl begins with a carpetlike double layer of NaCl film. 5 In an electron energy-loss scattering (EELS) measurement, Zielasek, Hildebrandt, and Henzler found electronic states at the NaCl/Ge interface and suggested that the dimerization of the Ge(100) surface is not eliminated at the NaCl/interfaceeven if the thickness of the NaCl rises to 20 monolaysers (MLs).…”
Section: Introductionmentioning
confidence: 99%
“…Quantum-optical effects, such as Hanbury Brown and Twiss [12], or Hong-Ou-Mandel interference [13], affecting the relative distribution of single photons, can be revealed only through measurement of photon-correlation functions. Second-order correlation functions have been recently investigated for diffraction gratings [14][15][16], and it was shown that the recurrence period of the second order spatial correlation function is twice larger than that of the light intensity. As MMI systems show periodical recurrences of the light inten- * Electronic address: eilon.poem@weizmann.ac.il sity, much like diffraction gratings, and as they can be rather easily miniaturized and integrated in photonic circuits [9,11], it is interesting to study the behavior of correlation functions in these systems.…”
mentioning
confidence: 99%